The Antioxidant and Anticancer Effects of Wild Carrot Oil Extract. (20th July 2012) - Shebaby, Wassim Nasri; El‐Sibai, Mirvat; Smith, Kikki Bodman‐; Karam, Marc Christoph; Mroueh, Mohamad; Daher, Costantine F.
Abstract : Daucus carota L. ssp. carota (Apiacea) is used in traditional medicine in Lebanon and in different regions throughout the world. The present study investigates the in vitro anticancer activities of Daucus carota oil extract (DCOE) on four human cancer cell lines as well as its in vitro antioxidant activity. DCOE was extracted from the dried umbels with 50:50 acetone‐methanol. The oil extract was analyzed by gas chromatography–mass spectrometry and screened for its antioxidant properties in vitro using 1, 1‐diphenyl‐2‐picryl hydrazyl free radical scavenging assay (DPPH), ferrous ion chelating assay (FIC) and the ferric reducing antioxidant power assay (FRAP). The anticancer activity of the oil extract against human colon (HT‐29, Caco‐2) and breast (MCF‐7, MDA‐MB‐231) cancer cell lines was evaluated using the trypan blue exclusion method and the WST‐1 cell proliferation assay. DCOE exhibited antioxidant activity in all assays used. The FRAP value was 164 ± 5.5 µmol FeSO4 /g, and the IC50 values for DPPH and FIC assays were 2.1 ± 0.03 mg/ml and 0.43 ± 0.02 mg/ml, respectively. Also, DCOE demonstrated a significant increase in cell death and decrease in cell proliferation. The effect of DCOE on the cell lines exhibited time and dose‐dependent responses. The present study established that DCOE possesses both antioxidant and promising anticancer activities. Copyright © 2012 John Wiley & Sons, Ltd.